Perilaku Self Injury Mempengaruhi Resiko Bunuh Diri pada Mahasiswa Tingkat IV Ilmu Keperawatan (S1) - Arifin, Berlyana Ulia; Inayah, Iin; Oyoh, Oyoh (Jurnal Keperawatan Komplementer Holistic, 2025)
Individuals who experience stressors continuously can gradually experience mental health problems, leading to negative/maladaptive responses. One such behavior is self-injury and the risk of suicide. Data from Australia indicates that 20% of people aged 18-24 have self-injured, while the figure for Indonesians is 36%. Deaths among adolescents (15-29) are the second leading cause of suicide. Self-injury can reduce anxiety about death and increase the potential for suicide attempts. Therefore, this research is highly urgent. Objective: To identify the relationship between self-injury behavior and suicide risk. This study used a cross-sectional approach. The population was 166 fourth-year Nursing students (S1) of FITKes UNJANI. Sampling was conducted using probability sampling techniques, specifically proportional random sampling, resulting in 117 respondents. The instruments used were the Self-harm Inventory (SHI) and the Beck Scale for Suicide Ideation (BSS). Data were collected using a questionnaire. Univariate analysis used frequency distribution, and bivariate analysis used the Spearman rank test. This study showed that almost all respondents had self-injured in the mild category (91 respondents (77.8%), and most respondents were at low risk of suicide (83 respondents (70.9%). There was a moderate and positive correlation between self-injury and suicide risk (R = 0.546 and p-value = 0.001 <0.05). Conclusion: There is a moderate and positive correlation between self-injury behavior and suicide risk. It is recommended that academic advisors play an active role and provide students with constructive/positive stress coping mechanisms.